Introduction to Sports Specialization: Historical Experience and Modern Models of Interaction Between Public Organizations in the Field of Physical Culture and Sports - Igor Hubariev; Svetlana Donchenko; Lyubov Kvitka-Yezhova (Scientific Journal of National Pedagogical Dragomanov University Series 15 Scientific and pedagogical problems of physical culture (physical culture and sports), 2026)
The article examines the theoretical and organizational principles of the functioning and interaction of sports public organizations in Ukraine. The classical vertical hierarchy of interaction between the Ministry of Youth and Sports of Ukraine, the national federation, regional branches, and grassroots links (clubs, youth sports schools) is analyzed. Special attention is paid to the newest historical stage of domestic sports development under the conditions of the full-scale invasion (since 2022). The forced change in the geography of competitions with the relocation of draughts life centers to safer regions (in particular, the experience of Kamianske), the introduction of online platforms for training and tournaments, as well as processes of adaptation to blackouts and staff shortages due to migration and mobilization are highlighted. The transformation of the functions of sports organizations is considered, which, in addition to training and competition activities, integrated socio-psychological adaptation of IDPs, rehabilitation of wounded military personnel, and a large-scale children's volunteer movement "We Play – We Help" to raise funds for the needs of the Armed Forces of Ukraine into their work. It is substantiated that to increase the efficiency of Ukrainian sport on the international arena and overcome internal crises, decentralization of management, expansion of the autonomy of local branches, and consolidation of efforts of independent sports NGOs are necessary. The materials of the article are of practical importance for the formation of professional competencies of future managers and coaches in the field of physical culture and sports.